Swamp of the hideous zombies - Hayes, Geoffrey (New York : Random House, 1996)
When a creepy fortune-teller moves into Boogie Bay one by one people begin to disappear, Otto feels sure zombie monsters are at work.
Keywords: Monsters -- Fiction; Horror stories